SafeCandy: System for security, analysis and validation in Android (2015)
Android is an operating system which currently has over one billion active users for all their mobile devices, a market impact that is influencing an increase in the amount of information that can be obtained from different users, facts that have motivated the development of malicious software by cybercriminals. To solve the problems caused by malware, Android implements a different architecture and security controls, such as a unique user ID (UID) for each application, while an API permits its distribution platform, Google Play applications. It has been shown that there are ways to violate that protection, so the developer community has been developing alternatives aimed at improving the level of safety. This paper presents: the latest information on the various trends and security solutions for Android, and SafeCandy, an app proposed as a new system for analysis, validation and configuration of Android applications that implements static and dynamic analysis with improved ASEF. Finally, a study is included to evaluate the effectiveness in threat detection of different malware antivirus software for Android.